Godly accountability: reflection on ethics for zakat accountants - Faris Shalahuddin Zakiy; Fitra Istianah Turahman (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - This research aims to explore the forms of accountability of zakat institutions and their importance and to uncover the meaning of accountability from zakat accountants.Method - To achieve this goal, this study uses qualitative methods with a phenomenological approach. There are three key informants interviewed in this study. Data analysis in this study was divided into four stages: bracketing, noema, noesis, and eidetic reduction.Result - This study found that accountability is reflected in financial reporting and accountability is essential for zakat institutions to increase good governance and trust in the community. Accountability can be interpreted as having faith and ethics, righteousness, accountability to God, and accountability to humans.Implication - Internalizing ethics to become a zakat accountant is more honest and professional and upholds integrity in carrying out its duties.Originality - This research discusses the meaning of accountability from zakat accountant’s perspective and forms of accountability in zakat institutions. Empirical findings can be used to develop insight into accountability in zakat institutions.